1984
DOI: 10.1161/01.cir.70.6.951
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the postexercise response of systolic blood pressure in the diagnosis of coronary artery disease.

Abstract: The normal decline in systolic blood pressure (SBP) during the recovery phase of treadmill exercise does not occur in some patients with coronary artery disease (CAD). In others the recovery values of SBP exceed the peak exercise values. To examine the diagnostic value of this observation, we studied 31 normal subjects and 56 patients undergoing treadmill exercise before coronary cineangiography. Because of large differences in peak exercise pressures between the two groups, recovery ratios were derived by div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…24 Furthermore the results in patients with coronary heart disease may differ from those of other subjects because of their medical treatment and because postexercise blood pressure appears to be influenced by the extent of coronary heart disease and of the possible exercise-induced impairment of left ventricular function. [15][16][17][18][19][20] The lower blood pressure on standing on the exercise day compared to the control day is compatible with the observation that orthostatic tolerance is impaired during the first half hour of recovery after exercise. 3 The results on subsequent ambulatory monitoring agree with those in healthy normotensive subjects, in whom ambulatory 10,12,14 or home 11 measurements of blood pressure showed that any blood pressure fall immediately after exercise was not sustained during the rest of the day.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…24 Furthermore the results in patients with coronary heart disease may differ from those of other subjects because of their medical treatment and because postexercise blood pressure appears to be influenced by the extent of coronary heart disease and of the possible exercise-induced impairment of left ventricular function. [15][16][17][18][19][20] The lower blood pressure on standing on the exercise day compared to the control day is compatible with the observation that orthostatic tolerance is impaired during the first half hour of recovery after exercise. 3 The results on subsequent ambulatory monitoring agree with those in healthy normotensive subjects, in whom ambulatory 10,12,14 or home 11 measurements of blood pressure showed that any blood pressure fall immediately after exercise was not sustained during the rest of the day.…”
Section: Discussionsupporting
confidence: 78%
“…[10][11][12]14 Similar results have been obtained in hypertensives, 11,13 but other studies 10,12,14 observed that hypotension was sustained for about 5 to 13 h after exercise. Studies in coronary artery disease concentrated on blood pressure measured during 3 to 5 min after exercise testing in order to improve the detection of ischaemia or to assess disease severity, [15][16][17][18][19][20] but we found no studies on the effect of a single bout of aerobic exercise or rehabilitation exercise training on blood pressure during longer periods of time and certainly not for 24 h after exercise in patients with coronary artery disease. An increasing number of cardiac patients are participating in rehabilitation programmes, in which the exercise intensity may be rather high.…”
Section: Introductionmentioning
confidence: 89%
“…It has been suggested previously that abnormal SBP response is an important indicator for coronary artery disease not only during exercise but also during the recovery phase. 14,24,25 Some studies observed that an abnormal ratio of recovery to peak exercise was even more sensitive than exercise-induced angina or ST depression for diagnosing the †Pack years denotes the lifelong exposure to smoking that was estimated as the product of years smoked and the number of tobacco products smoked daily at the time of examination. ‡Diabetes was defined as fasting blood glucose Ն6.1 mmol/L or a clinical diagnosis of diabetes with dietary, oral, or insulin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…severity of coronary artery disease. 24,25 In patients with angina pectoris, an abnormal SBP response during recovery was very sensitive for the diagnosis of multivessel coronary artery disease, suggesting the close correlation between this response and the severity of CHD. 14 Elevated SBP response during the exercise anticipation phase and attenuated SBP responses after exercise were related to increased risk of hypertension 6,21 and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in collaboration with the study carried out by Davis and Brown, 2001 18 . Amon et al, (1984) 19 in their study reported that during treadmill exercise in the normal subjects, systolic blood pressure is expected to rise to between 5 to 10 mmHg per metabolic equivalent of effort. A decrease in the diastolic blood pressure was recorded in this study and this could be attributed to the vasodilatation of arterial blood vessels in response to the exercise bouts.…”
Section: Discussionmentioning
confidence: 99%